The Anti-urolithiatic effect of the roots of Saussurea costus (falc) Lipsch agonist ethylene glycol and magnesium oxide induced urolithiasis in rats - Naima Mammate; Fatima Ezzahra El Oumari; Hamada Imtara; Salim Belchkar; Ramzi A. Mothana; Hinde E.L. Fatemi; Mohammed Danouche; Sara Er-rahmani; Nabil Boucetta; Omar M. Noman; Mahmoud Tarayrah; Tarik Sqalli Houssaini (Elsevier, 2024)
Phytotherapy, which involves the use of plant extracts and natural compounds for medicinal purposes, is indeed a promising alternative for managing urinary lithiasis. Many plants have been studied for their potential to prevent and treat kidney stones, and they may offer a more natural and potentially less harmful approach compared to conventional treatments. Additionally, phytotherapy may be more cost-effective. The aim of the present study was to investigate the antilithic potential of extracts and essential oils of Saussurea costus (Falc) Lipsch in two in vivo models, one on ethylene glycol-induced calcium oxalate crystal formation and the other to assess the effects of these extracts on magnesium oxide-induced struvite crystal formation. The experiment involved the administration of different doses of aqueous and ethanolic extracts of S. costus (200 and 400 mg/kg) and essential oils (25 and 50 mg/kg) to male Wistar rats, followed by the evaluation of various physiological, biochemical and histopathological parameters. The results demonstrated that the administration of S. costus essential oils and extracts had significant effects on the rats, influencing body weight, urine volume, crystal deposition, cytobacteriological examination of urine, and serum biochemical parameters. Histopathological examinations revealed varying impacts on the kidneys and livers of the treated rats. The findings suggest that S. costus extracts and essential oils may hold promise in inhibiting calcium oxalate crystal formation in vivo and influencing various physiological and biochemical parameters in rats. Overall, the 200 mg/kg ethanolic extract of S. costus demonstrated antilithiatic efficacy, did not exhibit signs of toxicity and reduced the number of crystals in the kidneys. Furthermore, the study did not find a significant effect on reducing struvite crystals.